Laura Carlevaris (a cura di). La ricerca nell’ambito della geometria descrittiva. Due giornate di studio. Roma: Gangemi Editore 2017 (diségno, 2018)
The book, edited by Laura Carlevalis and published by Gangemi Editore in 2017, includes the reports presented during the two days of study held on February 18 and 25 in the Ph.D. program in History, Design and Restoration of Architecture organized by the DSDRA of Sapienza University of Rome, and dedicated to the history and innovation of research in the area of Descriptive Geometry (read more).